2017
DOI: 10.1094/pdis-03-16-0371-re
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Characterization of Wheat Stripe Rust Fungus Puccinia striiformis f. sp. tritici in Ethiopia and Evaluation of Ethiopian Wheat Germplasm for Resistance to Races of the Pathogen from Ethiopia and the United States

Abstract: Stripe rust, caused by Puccinia striiformis f. sp. tritici, is one of the most important diseases of wheat in Ethiopia. In total, 97 isolates were recovered from stripe rust samples collected in Ethiopia in 2013 and 2014. These isolates were tested on a set of 18 Yr single-gene differentials for characterization of races and 7 supplementary differentials for additional information of virulence. Of 18 P. striiformis f. sp. tritici races identified, the 5 most predominant races were PSTv-105 (21.7%), PSTv-106 (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 24 publications
4
28
2
2
Order By: Relevance
“…We identified 14 breeding lines and two cultivars that were resistant to all races. Wan et al (2017) also identified several genotypes resistant at the seedling stage among the tested material, using two additional Pst races from Ethiopia and three from the United States.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 14 breeding lines and two cultivars that were resistant to all races. Wan et al (2017) also identified several genotypes resistant at the seedling stage among the tested material, using two additional Pst races from Ethiopia and three from the United States.…”
Section: Discussionmentioning
confidence: 99%
“…The seedlings were then transferred to a growth chamber with 16 h day at 16°C and 8 h night at 13°C. Six Chinese and one Ethiopian stripe rust races (culture EK3-12, Wan et al 2017) were used in the study. The virulence: avirulence profiles of the actual isolates of those races are given in Table 1.…”
Section: Seedling Testsmentioning
confidence: 99%
“…( Pst ), the causal agent of wheat stripe rust, is a serious threat to global wheat production (Boyd, 2005; Chen, 2005; Wellings, 2011). Virulence shifts in Pst population due to the genetic changes in existing local pathogen populations or migration of new races are major challenges to resistance breeding in wheat (Burdon, Barrett, Rebetzke, & Thrall, 2014; Chen, 2007; Hovmøller, Sørensen, Walter, & Justesen, 2011; Wan & Chen, 2014; Wan et al., 2016). Nearly US$1 billion is lost to Pst annually (Beddow et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The post‐2000 group of Pst races has broad‐spectrum virulence and increased aggressiveness and adaptation in warmer environments (Markell and Milus, 2008; Milus et al, 2009; Chen et al, 2010). In the US PNW, new races have been identified every year and race compositions are more diverse than any other region of the U.S. (Chen et al, 2010; Wan and Chen, 2012, 2014; Wan et al, 2017). Historically, PNW wheat breeders have incorporated multiple resistance genes for all‐stage resistance and adult‐plant resistance (APR) to develop more durable rust resistant wheat cultivars.…”
mentioning
confidence: 99%